2012
DOI: 10.1186/1476-072x-11-53
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of health system resources in relation to pandemic response capacity in the Greater Mekong Subregion

Abstract: BackgroundThere is increasing perception that countries cannot work in isolation to militate against the threat of pandemic influenza. In the Greater Mekong Subregion (GMS) of Asia, high socio-economic diversity and fertile conditions for the emergence and spread of infectious diseases underscore the importance of transnational cooperation. Investigation of healthcare resource distribution and inequalities can help determine the need for, and inform decisions regarding, resource sharing and mobilisation.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Data were collected as part of the AsiaFluCap Project, using survey tools as described in Hanvoravongchai et al . [ 17 ]. In brief, itemized healthcare resources were captured and quantified via questionnaires administered to all government-supported hospitals (n=185) and District Health Offices (DHOs) throughout all ODs (n=77) in Cambodia during March 2009 to September 2009.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected as part of the AsiaFluCap Project, using survey tools as described in Hanvoravongchai et al . [ 17 ]. In brief, itemized healthcare resources were captured and quantified via questionnaires administered to all government-supported hospitals (n=185) and District Health Offices (DHOs) throughout all ODs (n=77) in Cambodia during March 2009 to September 2009.…”
Section: Methodsmentioning
confidence: 99%
“…The results of these analyses, carried out at the Province level in all study countries, revealed high variability in resource capacities both between and within countries, with substantial avoidable mortality attributed to severe shortages in mechanical ventilators [ 12 ]. A follow-up analysis, focusing only on study countries in the Greater Mekong Subregion (Cambodia, Lao PDR, Thailand and Vietnam) mapped and analyzed key health care resource distributions at the Province level in order to identify relative resource shortages, mismatches, clustering, and inequalities in distribution [ 17 ]. Again, a high degree of heterogeneity in resource distribution was noted.…”
Section: Introductionmentioning
confidence: 99%
“…These articles also deal with the development of pertinent cartographic approaches to represent, for example, the risk linked to natural-focal diseases [ 38 ], or for better distributing healthcare resources in developing countries [ 39 ]. The scale of work seems to be different, the areas being bigger at a regional scale [ 40 ] or national [ 41 ], it is more about assessing or comparing health systems [ 42 ], access to healthcare [ 43 ] or health situations [ 44 ], transposing methods from a country to another rather than within a limited space where one tries to evaluate one’s ability to act on its inhabitants. The foregoing can partly explain the appearance of the terms countries , facilities and services in these articles.…”
Section: Discussionmentioning
confidence: 99%
“…The ASEAN Free Trade Area (AFTA) [ 4 ] and the ASEAN Economic Community were also formed to enhance ASEAN economic growth, to open a single market, and to achieve further expansion in international markets [ 2 ]. Moreover, these issues have repeatedly occurred in some countries for over decades because the same actions and measures have been employed and have failed to resolve the situation [ 5 ]. Previous studies have stated that there are many economic, environmental, and healthcare problems found in the GMS countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these issues have repeatedly occurred in some countries for over decades because the same actions and measures have been employed and have failed to resolve the situation [ 5 ]. Previous studies have stated that there are many economic, environmental, and healthcare problems found in the GMS countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%